Health Information-Seeking Behavior of Students at Kuwait University. Issue 4 (7th January 2022) - Aldousari, Elham; Al-Muomen, Nujoud
Abstract: This study aimed to investigate the health information-seeking behavior of Kuwait University undergraduates. The study employed a cross-sectional design using a semi-structured, web-based questionnaire. Most students (68.8%) searched for health information. The most common topics that students searched, by search engines, were related to bones, joints, and muscles. Many of the students (34.9%) discussed the health information they obtained on the Internet with physicians/medical specialists to consult health professionals. The study concluded that patients search for medical information from the Internet and that the doctor-patient relationship is influenced by the presence of health information on the Internet.